2015
DOI: 10.1038/ncomms8335
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic twins discordant for common variable immunodeficiency reveal impaired DNA demethylation during naïve-to-memory B-cell transition

Abstract: Common variable immunodeficiency (CVID), the most frequent primary immunodeficiency characterized by loss of B-cell function, depends partly on genetic defects, and epigenetic changes are thought to contribute to its aetiology. Here we perform a high-throughput DNA methylation analysis of this disorder using a pair of CVID-discordant MZ twins and show predominant gain of DNA methylation in CVID B cells with respect to those from the healthy sibling in critical B lymphocyte genes, such as PIK3CD, BCL2L1, RPS6KB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
76
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 45 publications
2
76
0
3
Order By: Relevance
“…By performing whole genome and RNA sequencing, interesting genes and pathways were found to be related to the CVID [52]. By examining genome-wide methylation sites, multiple genes were found to be hypermethylated in switched memory B cells of CVID patient, suggesting the potential role of defective demethylation in the development of CVID [58]. Though the latter two studies have the limitation of small sample size, they demonstrated the success of applying these novel high-throughput omics approaches to the study of the complex disease CVID.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…By performing whole genome and RNA sequencing, interesting genes and pathways were found to be related to the CVID [52]. By examining genome-wide methylation sites, multiple genes were found to be hypermethylated in switched memory B cells of CVID patient, suggesting the potential role of defective demethylation in the development of CVID [58]. Though the latter two studies have the limitation of small sample size, they demonstrated the success of applying these novel high-throughput omics approaches to the study of the complex disease CVID.…”
Section: Discussionmentioning
confidence: 98%
“…Many of these genes were further validated by pyrosequencing. [58][59][60] In addition to the identification of hypermethylated genes with potential contributions to the development of CVID, this study also demonstrated how studying monozygotic twins could significantly impact our understanding of the etiology of immune disorders.…”
Section: High-throughput Epigenomic Approachmentioning
confidence: 94%
See 1 more Smart Citation
“…The results presented support the notion of a complex basis of CVID and related milder PAD disorders, in which an accumulation of multiple genetic and/or environmental factors contributes to the final phenotype. 3,15,16 Monogenic defects have only been identified in a minority of cases with CVID. 14 Remarkably, some relatives with the same monogenic defect were found to be asymptomatic or suffer from a milder PAD phenotype such as IgGSD.…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, B cells in CVID patients have been shown to have DNA methylation alterations in genes critical for B-cell function, implicating a role for epigenetic factors in the pathogenesis of CVID. 16 While the immunological phenotype of CVID has been investigated in depth, there are only few reports on IPH and IgGSD and none on cohorts of asymptomatic PAD family members. We, therefore, performed a detailed immunophenotypic analysis of CVID, IPH and IgGSD patients as well as asymptomatic first-degree relatives of the PAD patients included in the study (asymptomatic family members, AFM) and unrelated healthy controls (HC).…”
mentioning
confidence: 99%